Comparative Study of Urinary Parameters in Different Conditions in Dogs - Tawfeeq, Mohammad Monir; Hanif, Nasirahmad; Minhaj, Mohammad Hamid (Journal of Natural Sciences – Kabul University, 2020)
Urinary diseases are among the most prevalent health issues in dogs. Various diagnostic methods, including radiography, ultrasonography, and hematology, are used for diseases affecting the urinary system. However, in many cases, the role of urinary parameters in urine samples is overlooked. This research examines urine samples from four dogs in different conditions: normal state, 0 hours after stress, 3 hours after stress, and 6 hours after stress. The results demonstrate a significantly higher amount of protein in the urine samples of stressed animals compared to normal animals. Other parameters, such as ketones, glucose, urobilinogen, pH, and specific gravity, were also elevated compared to normal animals. These findings suggest that stress can affect urinary parameters, which should be considered during laboratory examinations.